REHABILITASI SALURAN TARUM BARAT TERKAIT TATA RUANG WILAYAH JABODETABEK - Made Sumiarsih; Djoko Legono; Robert Kodoatie (Eco Rekayasa: Jurnal Teknik Sipil, 2015)
West Tarum Canal (WTC) is a canal to convey water for irrigation to the surroundings area  and for distributing raw water to Jakarta area. The total length of WTC is 69.8 miles, starting from the Curug weir to the Ciliwung River. WTC has been operated for 40 years. Recently, there has been a decline in function of this canal up to 70%. For that reason, this canal is required rehabilitation to restore it function. This paper highlights the planning and implementation of the rehabilitation work related to spatial planning of Jabodetabekpunjur.